A Parametric Statistics as A Supporting Tool to the Social Sciences - Goulionis, John E.; Stengos, Dimitrios I. (Journal of Informatics and Mathematical Sciences, 2010)
Partially Observable Markov Decision Processes (POMDPs) have recently been suggested as a suitable model to formalizing the planning of educational management. In this paper, we discuss a specialization of POMDPs that is tailored to a frequently re-occurring type of educational management problem. Furthermore under some reasonable conditions it is shown that there exists an optimal policy in the class of control limit policies and we develop a solution procedure utilizing these properties of the specialized form.